PENGAJARAN BAHASA ARAB ILMU MA'ANI DI MADRASAH ALIYAH FIRDAUS PANGALENGAN KABUPATEN BANDUNG - Rustiman, Uus; Nur, Tajudin (Indonesian Collaboration Journal of Community Services (ICJCS), 2025)
This community service program aims to enhance students' understanding of ilmu ma’ani, a branch of balaghah in Arabic, at Madrasah Aliyah Firdaus Pangalengan. The program involved 11th and 12th-grade students through interactive lectures, discussions, and text analysis exercises. The pre-test results indicated varying levels of initial comprehension, highlighting the need for more effective teaching methods. Post-test results demonstrated significant improvement, with 70% of students achieving higher scores. Interviews with students and teachers confirmed that the applied teaching methods were highly beneficial in understanding ilmu ma’ani. In conclusion, this program positively impacted students’ comprehension and can serve as a model for Arabic language teaching in madrasahs